TO THE QUESTION OF ALLUSIONS IN THE NOVEL «A CANTICLE FOR LEIBOWITZ» BY WALTER MILLER JR. - Kozhakhmetov, A.B.; Kudritskaya, M.I.; Podavets, O.D. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2023)
The study of allusion was not widespread until the middle of the 20th century, when it was recognised as an explicit, direct reference, leading to much disagreement among scholars and varied classifications. In English literature, there has been a tradition of making numerous allusions to historical, biblical and mythological events for a long time. And Walter Miller Jr.'s "A Canticle for Leibowitz" contains many examples of allusions which have not been examined from scientific point of view. This article examines allusions in the novel “A Canticle for Leibowitz” by Walter Miller Jr. All examples of references to religion, history, mythology etc. in the novel are presented with explanation of their meaning and function.
Keywords: allusion; stylistic devices; expressive means; stylistics; types of allusion